Taxonomic resolution of fleabane species (Conyza spp.) based on morphological and molecular markers and their dispersion across soybean-cropping macroregions and seasons in Brazil - Kalsing, Augusto [UNESP]; Nunes, Felipe A.; Gotardi, Guilherme A.; Campos, Jaqueline B.; Schneider, Angelo A.; Tropaldi, Leandro [UNESP]; Velini, Edivaldo D. [UNESP]; Merotto, Aldo; Carbonari, Caio A. [UNESP] (Cambridge University Press (CUP), 2024)
The Conyza genus includes nearly 150 species, comprising closely related weedy species. Proper identification of Conyza spp. is essential to develop effective strategies for their management. The overlap of traits, species varieties, and the putative occurrence of hybridization hampers the identification of Conyza spp. and its management in agricultural and natural environments. Herein, we assessed five DNA barcodes and 32 morphological traits to classify Conyza spp. and survey their dispersion in soybean fields [Glycine max (L.) Merr.] in Brazil in 2019, 2020, and 2021. The Conyza accessions included two species, hairy fleabane [Conyza bonariensis (L.) Cronquist) and Sumatran fleabane [Conyza sumatrensis (Retz.) E. Walker], and each species comprised two varieties. The ITS and rps16-trnQ gene regions showed the ability to distinguish between the two Conyza species, while the matK, rbcL, and trnF-trnF gene regions were not polymorphic. Out of 32 morphological traits, phyllary color, involucre shape, capitulescence type, and inflorescence type were the most polymorphic and even reliable for taxonomic purposes. The combination of ITS or ITS+rps16-trnQ regions and the four morphological markers was able to discriminate 91% of the plants, except those of C. bonariensis var. angustifolia. These results support the taxonomic resolution between C. bonariensis and C. sumatrensis and are useful for other Conyza spp. and other closely related weedy species worldwide. Conyza sumatrensis was detected in 94% of soybean fields across macroregions and seasons in Brazil, while C. bonariensis was sparsely dispersed, mainly in the southern macroregion (MRS 1).
Keywords: DNA barcoding; hairy fleabane; ITS; morphology; phylogeny; rps16-trnQ; Sumatran fleabane; taxonomy